Anteseden Konflik Pekerjaan-Keluarga Dan Pengaruhnya Terhadap Kinerja Pegawai (Studi pada Bank Pemerintah di Wilayah Jateng dan DIY) - Sih Darmi Astuti; Tristiana Rijanti (Conference In Business, Accounting, And Management (CBAM), 2012)
The purposeof this studywas to examinethe work-family conflictin the role of employeeperformance. Factors tobeantecedentsaresupervisorsupport, family involvement, role overload, andreligiosity. Work-family conflictis analyzedin two dimensions, which is based on timeand behavior.Family involvementis measuredfrom thefamily supportandfamily demands, while the performanceof the two-dimensionalmeasuredas describedMacKenzieetal. andWilliam&Anderson, namelyin-role andextra-role. Theimpactofwork-family conflictiswellbeing, in-role performanceandextra- role performance. The respondentsof this studyareemployees ofgovernments banksin theSpecial Region ofYogyakartain Central Java. Data collectionmethodandsurveyas many as 311 questionnaires returned from the350 whichcan bedeployedandusedin the analysis ofas many as 232pieces. Purposiveandconvenience sampling was used in this study. Validity and reliabilitytestingperformedbeforetesting therelationship betweenvariables usingstructural equation models. The analysis usedin this studyusing a Maximum Likelihood (ML). The resultscontribute towork-family conflictliteraturein threeways. Firstwork-family conflictoccurs onlyby timeand behavior, andis influenced byrole overload. The second wasfamily involvementoccurringform offamily supportdue tohigherdemands ofhis family. The third wasextra-role performanceis influencedby thewelfare of employeesin the form ofsatisfaction andgood health, whilewelfareis affectedby the performance of in-role andin-role performanceis affecteda person’s abilityto solve problemsisthe focus or in other words that they are having a good problem focused coping will be able to complete the in-role performance.Keywords: religiosity, work-family conflict, family involvement, wellbeing, performance.